2019
DOI: 10.3390/cancers11020267
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Imaging Evaluation after Downstaging of Pancreatic Ductal Adenocarcinoma: A Multi-Center Study

Abstract: Introduction: Evaluation of pancreatic ductal adenocarcinoma (PDAC) after chemoradiotherapy downstaging is challenging due to computed tomography (CT) overestimation of tumor extension and residual vascular involvement, limiting access to surgery to some patients with potentially resectable tumors. With this study, we wanted to assess which radiological findings are most reliable at pre-operative imaging in the evaluation of PDAC after chemoradiotherapy in order to achieve complete resection. Methods: We retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…outlined the low accuracy of imaging diagnostic tools in the management of pancreatic cystic neoplasms. In a multicentric European study, Beleù et al in 2019 reported comparable findings using CT and MRI scan in the preoperative evaluation of patients with pancreatic adenocarcinoma 4 .…”
Section: Discussion and Reviewmentioning
confidence: 89%
“…outlined the low accuracy of imaging diagnostic tools in the management of pancreatic cystic neoplasms. In a multicentric European study, Beleù et al in 2019 reported comparable findings using CT and MRI scan in the preoperative evaluation of patients with pancreatic adenocarcinoma 4 .…”
Section: Discussion and Reviewmentioning
confidence: 89%
“…CT has a positive predictive value of non-resectability ranging from 89% to 100% while the positive predictive value of resectability is lower (45–79%) [ 19 ]. A meta-analysis compared fiveimaging methods (CT, MR, angiography, PET and ultrasound) in the evaluation of suspected pancreatic masses [ 20 ]. Authors observed that CT and MR have similar sensitivity and specificity for defining vascular invasion.…”
Section: Methodsmentioning
confidence: 99%
“…Jeon et al [100] demonstrated that a postchemoradiotherapy tumor size equal or smaller than 2 cm and decrease in tumor-venous contact are independently associated with R0 resection. The result by Beleù et al [103] showed that a 25 mm cut-off for tumor size corresponded to a 64% sensitivity, 78% specificity, and 69% accuracy in assessing R0 resection, and that each 5 mm increment of tumor major axis dimension corresponded to an odds ratio of 1.79 for R+ resection. Based on the above considerations, it has been suggested that a decrease in tumor size or vascular contacts, even partial or moderate, should prompt surgical exploration even in the case of initially locally advanced disease [96].…”
Section: Imaging Assessment Of Response To Therapy: Where Are We Headed?mentioning
confidence: 99%